Schaus Swallowtail, Papilio aristodemus ponceanus Schaus (Insecta: Lepidoptera: Papilionidae) - Jaret C. Daniels (EDIS)
EENY-387, a 3-page illustrated fact sheet by Jaret C. Daniels, describes this endangered large brown and yellow butterfly which is restricted to tropical hardwood hammocks and their associated margins in Florida. Includes selected references. Published by the UF Department of Entomology and Nematology, September 2006.